Finite-time boundedness and finite-time l2 gain analysis of discrete-time switched linear systems with average dwell time - Lin, Xiangze; Du, Haibo; Li, Shihua; Zou, Yun (Journal of the Franklin Institute, 2013)
In this paper, finite-time boundedness and finite-time l2 gain analysis for a class of discrete-time switched linear systems are investigated. Not only linear matrix inequality conditions for the system dynamics but also average dwell-time of switching signal is given to guarantee finite-time boundedness of discrete-time switched linear systems. Moreover, sufficient conditions which guarantee finite-time boundedness of discrete-time switched linear systems with a finite-time l2 gain are also presented. Detail proofs are given by using multiple Lyapunov-like functions. A numerical example is employed to verify the efficiency of the proposed method.